Analisis Kemampuan Representasi Matematis Peserta Didik Kelas XI SMA pada Materi Bunga Majemuk - Tri Mustikaningrum; Nurhanurawati Nurhanurawati; Caswita Caswita (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to describe the mathematical representation abilities of Grade XI students focusing on the topic of compound interest. Mathematical representation is one of the essential competencies in mathematics education, encompassing visual, verbal, and symbolic forms. This research employed a descriptive qualitative method, with data collected through essay-based tests and in-depth student interviews. The study population consisted of Grade XI students from SMA YP Unila Bandar Lampung. The findings revealed that most students were unable to accurately represent the concept of compound interest. Common errors included inaccuracies in modeling compound interest growth and a tendency to apply arithmetic approaches instead of exponential ones. These findings indicate that students’ mathematical representation abilities—particularly in symbolic and verbal forms remain low. Therefore, strengthening instructional strategies that support the structured and meaningful development of mathematical representation skills is necessary.